1988
DOI: 10.1002/bjs.1800751009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical glove perforation

Abstract: In a study to investigate the incidence and significance of surgical glove perforation, bacterial contamination of surgeons' hands and gloves before and after operation was measured and the gloves tested for damage. Perforations were found in 74 of 582 gloves (12.7 per cent) and occurred in 34.5 per cent of operations. Glove perforation did not influence bacterial counts on the surgeons' hands or on the outside of their gloves. A separate clinical study of 100 adult hernia repairs gave no evidence that perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 14 publications
3
53
2
3
Order By: Relevance
“…These results are quite similar to the other studies in which chances of infection due to manual handling of shunt system have been observed up to 12 to 20%. 9, 13,14,27,30 Exposure of Shunt System to the surgical Instruments It is also evident from our results thatdue to increase touching of the shunt system can be a source of higher risk of infection. Moreover exposure of shunt system to surgical instrument can also cause infection in children.…”
Section: Manual Handling Of Shunt Systemsupporting
confidence: 55%
“…These results are quite similar to the other studies in which chances of infection due to manual handling of shunt system have been observed up to 12 to 20%. 9, 13,14,27,30 Exposure of Shunt System to the surgical Instruments It is also evident from our results thatdue to increase touching of the shunt system can be a source of higher risk of infection. Moreover exposure of shunt system to surgical instrument can also cause infection in children.…”
Section: Manual Handling Of Shunt Systemsupporting
confidence: 55%
“…1,2 The rate of glove perforation has been investigated in various surgical specialities: 10% for open lung surgery, 3 12-24% for caesarean section, 4,5 28% for major gynaecological surgery, 5 26% for orthopaedic surgery 6 and 35% for general surgery. 7 Unnoticed glove perforations represent a potential risk of infection for the surgeon by prolonged exposure to blood or other body fluids. Surgeons tend to underestimate the risk of cross-infection during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding glove perforation risks to the patient's wound has been conflicting. Dodds and colleagues [5] have suggested that glove perforations pose a limited threat for surgical site infections due to the current emphasis on improved preoperative hand preparation. By contrast, Misteli and colleagues [9] concluded that surgical glove perforations were a risk factor for surgical site infection and recommended extended antibiotic prophylaxis as a precaution.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%